Sentiment Analysis of UINSU Students' Comfort Towards Trans Metro Deli Services at Taman Budaya Bus Stop Using the Naive Bayes Method - Nurhidayati Nurhidayati; Dea Syahfira Hasibuan; Lailan Sofinah Harahap (Fakultas Teknik Universitas Bhayangkara, 2024)
The large number of bus passengers at the Taman Budaya bus stop is one of the public transportation problems. Finding that the Metro Deli Bus Organizer is still operating. They are considered capable of meeting the requirements for choosing a mode of transportation. The purpose of this study is to determine the passenger transportation factors on the Trans Metro Deli Bus. The Trans Metro Deli Bus Passenger Transportation Factor is the purpose of this study. Data Collection Techniques Using Questionnaires Student comfort factors when using the Trans Metro Deli bus service. This study's methodology starts with problem identification and moves on to problem-solving techniques and assessment procedures. Respondents were given a questionnaire to fill out to collect data. The author of this study used Google Forms. The author of this study solved the problem using the Naïve Bayes algorithm. The Naïve Bayes algorithm model produces results with an accuracy of up to 71.43%, which is quite good. The accuracy results of 71.43% and approaching 100% show how accurate the sentiment analysis is using the Naïve Bayes classification. The accuracy results of 71.43% and approaching 100% show how accurate the sentiment analysis is using the Naïve Bayes classification. 'The bus took a long time to arrive' and 'didn't get a seat' were the most common negative reviews, indicating that some students felt uncomfortable. The Naïve Bayes results of the study showed that people who reviewed the Trans Metro Deli Bus expressed more positive opinions, with the highest score of 71.43%.